2017
DOI: 10.1371/journal.pone.0169769
|View full text |Cite
|
Sign up to set email alerts
|

BUTIMBA: Intensifying the Hunt for Child TB in Swaziland through Household Contact Tracing

Abstract: BackgroundLimited data exists to inform contact tracing guidelines in children and HIV-affected populations. We evaluated the yield and additionality of household contact and source case investigations in Swaziland, a TB/HIV high-burden setting, while prioritizing identification of childhood TB.MethodsIn partnership with 7 local TB clinics, we implemented standardized contact tracing of index cases (IC) receiving TB treatment. Prioritizing child contacts and HIV-affected households, screening officers screened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 27 publications
(45 reference statements)
5
40
1
Order By: Relevance
“…Our study ndings are consistent with other qualitative studies in Africa and South-East Asia, which found that community members supported the concept of HHCT 11,18,22,23 . A common reason for appreciation of TB services at home was it removed barriers of access and cost.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study ndings are consistent with other qualitative studies in Africa and South-East Asia, which found that community members supported the concept of HHCT 11,18,22,23 . A common reason for appreciation of TB services at home was it removed barriers of access and cost.…”
Section: Discussionsupporting
confidence: 92%
“…Community members did not have to travel long distances to access clinic services. Despite the overall positive attitude in these studies 11,18,22,23 , there have been examples in South Africa where HHCs were not comfortable with home visits from research staff, speci cally concerned with associated stigma and the opinions of their community members 22 . In contrast, our study participants did not express this same concern implying that there was no stigma attached to HHCT.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…11 It is invaluable in the TB program, and has been recommended as a strategy to increase TB case finding for many years. 14,15 Contact tracing follows the identification of a tuberculosis index case, and it is an important strategy for the early identification and treatment of childhood tuberculosis, and for the provision of prophylaxis for cases with a high risk of progression of disease. 16 This prophylaxis involves Isoniazid Preventive Therapy (IPT), and the initial targets are those at most risk of disease progression, such as young children and human immunodeficiency virus (HIV) infected individuals in contact with an infectious adult with TB.…”
Section: Discussionmentioning
confidence: 99%
“…Household tracing of child contacts has been widely recommended by global health organizations and disease experts for over a decade [10][11][12] because child contacts have a high yield of both Mycobacterium tuberculosis infection and disease. [13][14][15][16] Despite this, contact tracing has been implemented poorly or not at all in high-burden, lowincome settings. 11,17 For example, <20% of contacts of tuberculosis patients diagnosed in Ethiopia were programmatically screened for disease.…”
Section: Introductionmentioning
confidence: 99%